2020
DOI: 10.3390/w12020356
|View full text |Cite
|
Sign up to set email alerts
|

Chorological and Ecological Differentiation of the Commonest Leech Species from the Suborder Erpobdelliformes (Arhynchobdellida, Hirudinea) on the Balkan Peninsula

Abstract: This study is the result of extensive investigations of leeches on the Balkan Peninsula. Our aim was to detect actual and potential (modeled) distributions of common Erpobdellidae species, and to identify their ecological differentiation with respect to the altitudinal and waterbody type gradient. Although widespread, these species rarely live together. Intense competition is avoided by preferences for different types of habitats. This was confirmed by Pearson correlation analyses that yielded negative results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Further, D. lineata has been recorded from several countries in the southwestern parts of the western Palearctic (Marinković et al, 2020;Nesemann & Neubert, 1999), including western Iran (Bennike, 1940;Grosser & Pešić, 2006;Salimi et al, 2011). Curiously, but likely due to the wide distribution of the species across southern deltas and high elevations in the Caspian region and northwestern and western mountainous regions, the species delimitation analysis considered the Iranian northeastern and northwestern populations of (see Grosser, 2015;Nesemann & Neubert, 1999).…”
Section: Dna Barcoding Of Erpobdellidaementioning
confidence: 99%
“…Further, D. lineata has been recorded from several countries in the southwestern parts of the western Palearctic (Marinković et al, 2020;Nesemann & Neubert, 1999), including western Iran (Bennike, 1940;Grosser & Pešić, 2006;Salimi et al, 2011). Curiously, but likely due to the wide distribution of the species across southern deltas and high elevations in the Caspian region and northwestern and western mountainous regions, the species delimitation analysis considered the Iranian northeastern and northwestern populations of (see Grosser, 2015;Nesemann & Neubert, 1999).…”
Section: Dna Barcoding Of Erpobdellidaementioning
confidence: 99%
“…Grosser and Pešić with their associates have compiled checklists for Montenegro (2014) and Serbia (2015), and Dmitrović and Pešić made an updated checklist of leeches of Bosnia and Herzegovina [25,28,29] (Table 12.1). New insight on the ecology of leeches their preferences, communities and impact of ecological factors on them, with special attention on spring habitats, was provided by Marinković et al [32,33].…”
Section: History Of Leech Investigation In Western Balkansmentioning
confidence: 99%
“…Sket [47], based on limited data, suspected that in these territories the typical D. l. lineata would be common, but it was shown that it has very limited presence. New studies of erpobdellid leeches [33,34] have shown that D. dinarica is very common inhabitant of Balkan watercourses, and is one of the most common leech species of the region. Although it is found in all types of water ecosystems it is usually found in fast flowing mountainous springs and brooks, where it is seldomly accompanied by other leech species [32,34].…”
Section: Erpobdellidaementioning
confidence: 99%
See 1 more Smart Citation
“…Visoko; river Miljacka (Sarajevo); river Bosna (above Visoko); river Bosna (below Ilijaš); river Bosna; river Bosna (Ilijaš); river Bosna (]ošanice); river Trebišnjica (Trebinje); river Bosna (Relstvo); river Vrbas (Bugojno); Bačevići; river Una; river Vrbas (Delibašino village); river Sana (Dragotinja); river Bosna (Gošce); river Neretva (Čapljina); the mouth of river Sana Šapkarev (1978) River Una near the mouth of the river Sana; river Una (Dubica) Cvijić & Blagojević (1985) as "Herpobdella octoculata" River Una (lower part); river Vrbas; river Bosna (lower part); river Drina; river Sava Marinković et al (2020) Erpobdella testacea (Savigny, 1820)…”
Section: Taxa Localities Referencesmentioning
confidence: 99%